THE NEW FIXED COMBINATION OF AMLODIPINE AND RAMIPRIL IN THE TREATMENT OF HYPERTENSION - V. I. Podzolkov; A. I. Tarzimanova (Рациональная фармакотерапия в кардиологии)
Just a small part of hypertensive patients is treated effectively despite the wide variety of antihypertensive drugs. Combined antihypertensive therapy can solve the problem of influence on the various pathogenic mechanisms of hypertension. The combination of an ACE inhibitor and a dihydropyridine calcium channel blocker is one of the most efficient, since both groups of drugs act as vasodilators and have therapeutic synergy in blood pressure reduction. A fixed combination of ramipril with amlodipine is an effective antihypertensive drug with a good tolerability profile. It effectively provides both blood pressure control and positive cardioprotective and nephroprotective effect.